2014
DOI: 10.1161/strokeaha.114.004285
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Burden, Neuroinflammation, and Links to Cognitive Decline After Ischemic Stroke

Abstract: O ne in 5 patients with stroke will end up demented shortly after a stroke, half with prior cognitive impairment and half without. After recurrent stroke, more than a third will become demented. 1 The mechanisms remain unclear beyond the fact that neurodegenerative and vascular mechanisms contribute to the cognitive decline.2 In this review, we explore experimental and clinical evidence of interaction between ischemia, amyloid deposition, and neuroinflammation and identify new potential therapeutic targets. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 51 publications
2
107
0
1
Order By: Relevance
“…Moreover, it has been demonstrated that the ischemic milieu triggers Ab deposition in the CNS (47,48). Our data report that Ab aggregates frequently absorb GFAP molecules, suggesting that clasmatodendrosis affects Ab deposition on neurons through the interaction between APJ fragments and Ab fibrils.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, it has been demonstrated that the ischemic milieu triggers Ab deposition in the CNS (47,48). Our data report that Ab aggregates frequently absorb GFAP molecules, suggesting that clasmatodendrosis affects Ab deposition on neurons through the interaction between APJ fragments and Ab fibrils.…”
Section: Discussionsupporting
confidence: 49%
“…Cytosolic cytochrome c release and caspase activation have been observed during ischemia-induced apoptosis (31) and NSCs are able to attenuate caspase-3 activation and impairment in OGD-treated BMECs. It has been demonstrated in vivo that NSCs affect the PI3K/Akt/GSK3β pathway, which regulates cell proliferation, survival and migration (14,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…27 Accordingly, TIAs are known to be associated with an increased long-term risk of cognitive decline and dementia. 3,4 Independent from or in addition to this classic diminished reserve mechanism, neuronal death might also directly trigger aβ deposition and facilitate Alzheimer pathology, 40,41 an effect possibly enhanced in SHRs given their naturally occurring accelerated brain aging. Thus, SNL and MA might represent therapeutic targets in patients with TIAs.…”
Section: Discussionmentioning
confidence: 99%